The Antibacterial Activity Test using Ethyl Acetate Fraction from Kersen Leaves (Muntingia calabura L.) against the Staphylococcus aureus - Mutiara Fadilah; Mustika Weni; Sri Marfuati (GHMJ (Global Health Management Journal), 2026)
Background: Staphylococcus aureus is a common cause of skin and soft tissue infections (pyoderma) and has developed resistance to multiple antibiotics. Kersen (Muntingia calabura L.) leaves contain bioactive compounds such as flavonoids, triterpenoids, steroids, tannins, and saponins, which have been reported to possess antibacterial properties. Aim: This study aimed to evaluate the in vitro antibacterial activity of the ethyl acetate fraction of M. calabura leaves against S. aureus. Methods: An experimental study with a post-test-only control group design was conducted. Phytochemical screening was performed to identify the secondary metabolites present in the fraction. Antibacterial testing was done using the well diffusion method on Mueller-Hinton Agar (MHA). Five treatment groups (ethyl acetate fractions at concentrations of 100%, 60%, 20%, 10%, and 1%) were compared to a negative control (10% DMSO) and a positive control (doxycycline). Inhibition zones were measured manually in millimeters and analyzed using one-way ANOVA (p < 0.05). Results: The ethyl acetate fraction demonstrated a concentration-dependent antibacterial effect. Mean ± SD inhibition zones were 17.20 ± 1.92 mm (100%), 12.94 ± 1.13 mm (60%), 7.99 ± 0.70 mm (20%), 7.34 ± 0.35 mm (10%), and 6.71 ± 0.85 mm (1%). The positive control showed a significantly higher inhibition zone (33.82 ± 1.62 mm), while the negative control showed no inhibition. Phytochemical screening of the kersen leaf ethyl acetate fraction includes tannins, saponins, steroids, triterpenoids, and phenolics. Conclusion: The ethyl acetate fraction of M. calabura leaves exhibited antibacterial activity against S. aureus. These findings support its potential development as a plant-based antibacterial agent, although further in vivo studies are needed.